Impulsive and Compulsive Buying Tendencies and Consumer Resistance to Digital Innovations: The Moderating Role of Perceived Threat of COVID-19 - Li, Hung Xin; Hassan, Komal; Malik, Haider Ali; Anuar, Marhana Mohamed; Khan, Tariq Iqbal; Yaacob, Mohd Rafi (Frontiers in Psychology, 2022)
Established on the theory of reasoned action and Innovation resistance theory, this study aims to explore the tendencies of consumer resistance to digital innovation and the moderating role of a perceived threat of Covid-19. Data were collected using a cross-sectional online survey of 1000 consumers of Fast Moving Consumer Goods (FMCG) products in Pakistan. Results revealed several significant relationships between tendencies (impulsive and compulsive) of consumer resistance to digital innovation and the perceived threat of Covid-19. This study brings several key insights for consumers of FMCG products from Pakistan as well many theoretical and practical implications along with future research directions are suggested.